MANAJEMEN SARANA PRASARANA PENDIDIKAN ANAK USIA DINI DI TAMAN KANAK-KANAK - Rodah, Pelagia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this study is to describe, procure, inventory, use, maintenance, accountability, destruction of Infrastructure Education Infrastructure Management In Childrens Nurse Sister Pontianak. This research uses descriptive method with qualitative approach. The sample of this research is infrastructure in kindergarten Sister Pontianak. The results of data analysis show, planning, procurement, inventory, use, maintenance, accountability, destruction done by head of kindergarten according to base school. Infrastructure is very important in the world of education, infrastructure is very supportive to the implementation of teaching and learning process, infrastructure facilities in early childhood is an important media konket especially early childhood education in providing early childhood services to learners. Keywords: Infrastructure Management